2013
DOI: 10.29173/cais370
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Unifying Ontology for Human-Information Interaction

Abstract: Research agendas in human-information interaction (HII) are varied and divergent. The interdisciplinary lens of information studies offers a convergent view of HII scholarship. The purpose of this paper is to taxonomically document the divergent scholarship in human-information interaction, and construct a unifying ontology of HII discourse, using bibliometric techniques.Les programmes de recherche en matière d'interaction homme-information sont variés et divergents. L'interdisciplinarité des sciences de l'inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This was particularly notable when use of the term \KM" was considered in the post-2000 literature searching. Further investigation of these research results revealed an increase in KM discourse in the trade press for this period of time, and its embrace as an activity in almost a dozen other venues (Jank, 2010b). This breakdown is illustrated in Fig.…”
Section: Let Us Look At That Conclusionmentioning
confidence: 81%
“…This was particularly notable when use of the term \KM" was considered in the post-2000 literature searching. Further investigation of these research results revealed an increase in KM discourse in the trade press for this period of time, and its embrace as an activity in almost a dozen other venues (Jank, 2010b). This breakdown is illustrated in Fig.…”
Section: Let Us Look At That Conclusionmentioning
confidence: 81%
“…The researcher remained sensitive to possible bias during the coding process, and sought to triangulate the evidence as suggested by LeCompte and Schensul (1999), who state that any themes, patterns, or constructs do not arise magically from the transcripts, but rather, their "emergence" is the result of various types of evidence being thoughtfully and reflectively considered during the coding process. Jank (2010) suggests that this strategy for coding data, when carefully followed, can also increase the validity of the coding outcome. These directives influenced the coding of the transcripts for the study.…”
Section: Discussionmentioning
confidence: 99%
“…The relevant themes often emerge from the repeating ideas and related categories as the heart of the content analysis; they provide perhaps the most logical expression of the content's narrative, as it were. The grouping of themes also represents a type of naïve classification (Beghtol, 2003), and can provide a framework for future discourse and analysis (Jank, 2010). Taken together, these themes present a more cohesive overview of the focus groups' outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideas discussed in this paper are grounded in published scholarship that discusses physical objects as conveyors of ideational content in specific learning communities (Jank, 2010). The historic restoration of Colonial Williamsburg was selected for this qualitative study because it so closely fits the "extended metaphor of a work" (Smiraglia, 2004).…”
Section: Introductionmentioning
confidence: 99%